Hukum Penyaluran Zakat Mal Untuk Pembangunan Fasilitas Sekolah Dalam Perspektif Wahbah Az-Zuhaili (Studi Kasus Unit Pengumpulan Zakat Keluarga Abituren Musthafawiyah Kota Medan) - Asnisiyah Aruan; Rahmat Hidayat (LPPM Universitas Ekasakti Padang, 2023)
The zakat collection unit is tasked with collecting and distributing zakat funds to mustahiq zakat, but in its distribution in the Musthafawiyah Abituren Family Zakat Collection Unit distributes it to the construction of educational facilities, distribution outside the eight Asnaf is guided by MUI Fatwa No. 14 of 2011 concerning the Distribution of zakat assets in the form of managed assets. Zakat can only function when the collected zakat funds reach mustahiq, in the existing literacy mustahiq zakat consists of eight asnaf, all of which are understood by the majority of people, but in practice there are some zakat collectors who distribute the benefits of zakat to schools. Therefore, it is necessary to know what is the law of distributing zakat funds for the construction of school facilities. This research uses qualitative research with empirical juridical research type in which this research was conducted at the Musthafawiyah Abituren Family Zakat Collection Unit. From this research it is found that scholars have different views on the issue of distributing zakat to other than the eight asnaf, Wahbah Az-Zuhaili and the Jumhur scholars in the madhhabs agree that it is not permissible to distribute zakat to other than the asnaf determined by Sharia.